Aesthetics and creativity in e-learning material. (30th November 2011) - Duh, Matjaž; Krašna, Marjan
We do know that new learning material must be interactive and actively involve students in the learning process. The idea is generally good but the implementation sometimes falls behind. During the analysis of e-learning materials that are publicly available, we discovered some noticeable and subtle flaws in the materials. The contemporary design paradigm of e-learning materials requires products that are didactically useful and aesthetically appropriate. The quality assured development of e-learning materials should be a part of education in all pedagogical studies. Students who study special didactical disciplines should acquire a critical view of the application of e-learning materials through their own prepared presentations. This article presents a discussion on the aesthetic conditions for designing of e-learning materials. The fundamental parameters for the assessment of aesthetically suitable e-learning materials will be reviewed as well as options for involving students in the learning process.